Traceological analysis in South America: trajectories, methodologies and future perspectives - Cattaneo, Gabriela Roxana (Facultad de Filosofía y Humanidades. Museo de Antropología, 2023)
This work presents a brief historical synthesis - not exhaustive - of the works of functional analysis of lithic instruments with a microscopic base carried out in South America. Starting from three approaches, we propose to discuss the state of the question around this issue considering: 1) Trajectories: On the basis of a series of personal interviews, sketch an interpretation on perspective of the personal trajectories of the researchers who carry them out, trying to understand their training, the views, interests and approaches of their work; 2) Methodologies: Discuss the similarities and differences in their methodological approaches carried out on South American archaeological contexts by South American researchers initially trained in Europe and the US, and later in their countries of origin. In general, they have been linked mainly to two lines of research: on the one hand, theoretical-methodological studies, associated with the development of experimental programs, and on the other, to answer questions of a rather specific nature in the framework of regional archaeology work. The results of these and / or other approaches will be quantified through the analysis of the publications; 3) Future perspectives of this type of analysis: once the two previous topics have been assessed, a recapitulation and proposal of what would be the lines in development and their nuances is proposed.